Pelatihan keterampilan memperbaiki alat ukur di laboratorium pada Kelompok MGMP Fisika di Kota Parepare - Ahmad Yani; Sidin Ali; Mutahharah Hasyim (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The purpose of the training of physical measuring instrument improvement in laboratories in the MGMP Group ofPhysics of Parepare is to train and develop the skills of teacher physics in improving physical measuring instrument, especiallyelectrical measuring instrument. The methods used are training related to physical measuring instruments, measuring instrumentrepair, and monitoring and evaluation of the results obtained from the training. The external obtained from this activity is; (i)Participants knowledge of how to improve measuring instruments; (ii) The trainees of physics and Laboran teachers can improvethe physical measuring instruments in the laboratory, especially electrical measuring instruments; and (iii) experiences related tothe recognition instrument introduction of participants increased. The conclusion of this training is (i) increasing the teacher'sknowledge of the MGMP group Physics in the city of Parepare on how to improve the physics measuring instruments inlaboratories, especially electrical measuring instruments and (ii) Increase motivation, talent and interest as well as ability Physicsteacher in repairing physics measuring instruments.